Peningkatan Aktivitas dan Hasil Belajar Matematika Siswa SD melalui Metode Quantum Teaching pada Siswa Kelas III Sekolah Dasar - Muhamad Irfan Nawawi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Quantum teaching method applied in grade III sd Negeri Cinanas 03 Bantarkawung Subdistrict Brebes aims to improve the activities and results of students' mathematics learning. This research is conducted in 2 cycles with stages of each cycle, namely planning, implementation, observation, and reflection. The subjects of this class action study were teachers and grade III students of SD Negeri Cinanas 03 with a total of 30 students consisting of 13 male students and 17 female students. Data collection tools use observation sheets and technical formative tests of data analysis using qualitative and quantitative analysis techniques.  The results showed that the application of quantum teaching approach model can improve students' mathematical learning activities and results. This can be seen from the student's learning achievements reaching the completion level gradually from pre-cycle (40%), cycle I (60%) and up to cycle II (83.33%). The activity of learning students reach a level of completion.